Analisis Strategi Sosiologi Dakwah dalam Menghadapi Problem Sosial Masyarakat - Ahmad Abuzar; Nurunniyah Nurunniyah; Dinda Mulyani Anjani (Lembaga Pengembangan Kinerja Dosen, 2025)
Sociological da'wah strategy as a scientific approach in answering social problems in society. Sociology of da'wah not only conveys Islamic values, but also pays attention to social, cultural, and societal change aspects. This article presents the thoughts of Muslim sociologists, the development of da'wah theory, and the challenges and opportunities of da'wah in the modern era. Through a qualitative descriptive approach and literature study, this study shows that sociological-based da'wah strategies can increase the effectiveness of religious messages and strengthen positive social change in society.